The land and people of Cambodia - Chandler, David P. (David Porter), 1933- (New York, NY : HarperCollinsPublishers, 1991)
Introduces the history, geography, people, culture, government, and economy of Cambodia.
Starting from zero -- The land -- The people -- Cambodia's early history -- Kingship and society at Angkor -- Cambodia's search for independence -- From colonialism to independence -- From independence to revolution -- Revolution in Cambodia -- Cambodia since 1979 -- Cambodia today.
Content of this book vary slightly from the book of the same title published in 1972.
Includes bibliographical references : (page 196-201) and index.
Filmography : page 201.
Discography : page 201.
Keywords: Cambodia -- Juvenile literature